1988
DOI: 10.1007/bf00417260
|View full text |Cite
|
Sign up to set email alerts
|

Plasma lecithin: cholesterol acyltransferase activity in elite athletes from selected sports

Abstract: The activity of lecithin: cholesterol acyltransferase (LCAT) and the plasma lipoprotein concentrations of elite athletes from 8 selected sports (volleyball, judo, sprinting, wrestling, throwing, cycling, water polo and tennis) were determined and compared with those of a sedentary control group. Plasma LCAT activity levels in the athletes were significantly 2.2-7.0 times higher than in the controls in most sports (p less than 0.01). Judo, sprinting, wrestling and throwing had comparable LCAT values while tenni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 18 publications
2
7
0
Order By: Relevance
“…28 This process is mediated by cholesterol ester transfer protein; however, the role of this enzyme is difficult to discern, as both an increase 27 and decrease 29 have been reported with exercise training. A similar situation is evident with lecithin cholesterol acyltransferase, as either an increase 30 or no change 31 has been observed with training intervention; however, a decrease in hepatic lipase activity is evident with physical activity.…”
Section: Discussionsupporting
confidence: 55%
“…28 This process is mediated by cholesterol ester transfer protein; however, the role of this enzyme is difficult to discern, as both an increase 27 and decrease 29 have been reported with exercise training. A similar situation is evident with lecithin cholesterol acyltransferase, as either an increase 30 or no change 31 has been observed with training intervention; however, a decrease in hepatic lipase activity is evident with physical activity.…”
Section: Discussionsupporting
confidence: 55%
“…Small intestine and liver ATP contents were determined by Bioaffina GmbH (Germany) ATP sensitive Bioluminescence kit. Plasma preb HDL was separated according Ishida et al (Tsopanakis et al 1988) agarose electrophoresis method, and then assaying ApoA1 in preb HDL band was done using Rat ApoA1 Enzyme immunoassay kit (Wuhan USCN Sciences Co Ltd, Wuhan, China).…”
Section: Lipids and Lipoproteinsmentioning
confidence: 99%
“…It was shown that acute exercise, exercise training, and fitness can favorably affect the several key steps in RCT such as Enhanced cellular cholesterol efflux (Brites et al 2004), increased formation and size of Apo A-I (Wilund et al 2002;Olchawa Beata 2004), increased plasma pre-b HDL levels (Jafari et al 2003;Sviridov et al 2003), increased LCAT activity (Cumhur Kilinç et al 2000;Olchawa Beata 2004;Tsopanakis et al 1988), and increased HDL-C level (Durstine et al 2001). But studies to examine the effect of exercise training on ABCA1 are really rare.…”
Section: Introductionmentioning
confidence: 97%
“…In addition, heparin administration and corporal training increase the LCAT activity (Tsopanakis et al 1988;Tsopanakis and Tesserommatis 1991).…”
Section: Discussionmentioning
confidence: 99%